DEPICTING THE SIGNIFICANCE OF ICT IN THE SUSTENANCE OF NATIONAL SECURITY: A REVIEW OF THE IMPORTANCE OF TECHNOLOGY IN GLOBAL SOCIETY - Adeolu AGOI, Moses; Sain, Zohaib Hassan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
It is obvious in clear terms that there is a significant relationship between ICT and national security (Snow, 1987). Information and Communication Technology (ICT) is an umbrella term that encompasses the function of unified communications and harmonized telecommunications including software applications, storage and audio-visual systems that enable users to process information. ICT can therefore play an importance role in national safety and defence against instability and risks violence brought about by rapid technological growth, social and political transformation. This paper is a descriptive review of the role of ICT in the overall security of a nation. The paper discusses the concept of ICT and security. It further identifies the problems faced by ICT implementation and possible solutions for the sustainance of national security. In order to collect importance data for the paper discussion, questionnaire instrument were administered to respondents using online Google form. The gathered responses were subjected to reliability analysis. In conclusion, recommendations were made.